An unprecedented water stable acylamide-functionalized metal–organic framework for highly efficient CH4/CO2 gas storage/separation and acid–base cooperative catalytic activity. Issue 9 (14th August 2018) - Zheng, Baishu; Luo, Xin; Wang, Zhaoxu; Zhang, Shaowei; Yun, Ruirui; Huang, Lu; Zeng, Wenjiang; Liu, Wenlong
Abstract : HNUST-8 exhibits water stable, efficient CH4 /CO2 storage and separation, acid–base cooperative catalytic activity in a tandem deacetalization Knoevenagel densation. Abstract : The high porosity, excellent water stability and optimized supramolecular host–guest interactions of MOFs are the three key factors for their potential practical applications in many important areas including gas storage/separation, catalysis and so on. In this study, we designed and constructed a highly porous (3, 36)-connected txt -type acylamide-functionalized metal–organic framework (HNUST-8) from a pyridine-based acylamide-linking diisophthalate and dicopper(ii )-paddlewheel clusters. Interestingly, HNUST-8 possesses an exceptionally water-stable framework with a high BET surface area of about 2800 m 2 g −1 . At 298 K, HNUST-8 exhibits a high excess CO2 uptake of 19.7 mmol g −1 at 40 bar, an excellent total CH4 storage capacity of 223 cm 3 (STP) cm −3 with a large working capacity of 178 cm 3 (STP) cm −3 at 80 bar, as well as highly efficient CO2 /CH4 and CO2 /N2 separation under dynamic conditions at 1 bar. Moreover, with the Lewis acidic open copper(ii ) sites and Lewis basic acylamide groups integrated into the framework, HNUST-8 demonstrates efficient catalytic activity as an acid–base cooperative catalyst in a tandem one-pot deacetalization–Knoevenagel condensation reaction.